Nekaj misli o regiji - Plazar Mlakar, Manca (Urbani izziv, 2000)
The region is a multi-layered concept. It presents a conglomerate of local communities in a nation state, connections between countries or sub-national entities on a supranational level, connections between geographical homogenous areas, as well as connections between geographically close or distant areas with similar problems into problem or interest region. Separate concepts are planning regions, devised to perform various development policies, conceptual regions or regional unions. With respect to different forms and typologies, the concept of regions is dealt with as a systematic union of units on the lower level, as an entity with specific characteristics that enable specific modes for their self-organisation and the organisation oftheir own structures and processes.
Keywords: prostorsko urejanje; regije; regionalno planiranje; tipologija